CCR5 Blockade in Inflammatory PML and PML-IRIS Associated With Chronic Inflammatory Diseases' Treatments. Issue 1 (2nd January 2022) - Bernard-Valnet, Raphael; Moisset, Xavier; Maubeuge, Nicolas; Lefebvre, Mathilde; Ouallet, Jean-Christophe; Roumier, Mathilde; Lebrun-Frenay, Christine; Ciron, Jonathan; Biotti, Damien; Clavelou, Pierre; Godeau, Bertrand; Du Pasquier, Renaud A.; et al.
Abstract : Background and Objectives: Progressive multifocal leukoencephalopathy (PML) is a disabling neurologic disorder resulting from the infection of the CNS by JC polyomavirus in immunocompromised individuals. For the last 2 decades, increasing use of immunotherapies leads to iatrogenic PML. Iatrogenic PML is often associated with signs of inflammation at onset (inflammatory PML) and/or after treatment withdrawal immune reconstitution inflammatory syndrome (PML-IRIS). Although immune reconstitution is a key element for viral clearance, it may also be harmful and induce clinical worsening. A C-C chemokine receptor type 5 (CCR5) antagonist (maraviroc) has been proposed to prevent and/or limit the deleterious immune responses underlying PML-IRIS. However, the data to support its use remain scarce and disputed. Methods: We conducted a multicenter retrospective cohort study at 8 university hospitals in France and Switzerland by collecting clinical, biological, and radiologic data of patients who developed inflammatory PML (iPML) or PML-IRIS related to immunosuppressive therapies used for chronic inflammatory diseases between 2010 and 2020. We added to this cohort, a meta-analysis of individual case reports of patients with iPML/PML-IRIS treated with maraviroc published up to 2021. Results: Overall, 27 cases were identified in the cohort and 9 from the literature. Among them, 27 met the inclusion criteria: 16 treated with maraviroc and 11 with standard of care (including corticosteroids use). Most cases were related to MS (92.6%) and natalizumab (88%). Inflammatory features (iPML) were present at onset in 12 patients (44.4%), and most patients (92.6%) received corticosteroids within the course of PML. Aggravation due to PML-IRIS was not prevented by maraviroc compared with patients who received only corticosteroids (adjusted odds ratio: 0.408, 95% CI: 0.06–2.63). Similarly, maraviroc did not influence time to clinical worsening due to PML-IRIS (adjusted hazard ratio = 0.529, 95% CI: 0.14–2.0) or disability at the last follow-up (adjusted odds ratio: 2, 95% CI: 0.23–17.3). Discussion: The use of CCR5 blockade did not help to keep deleterious immune reconstitution in check even when associated with corticosteroids. Despite maraviroc's reassuring safety profile, this study does not support its use in iPML/PML-IRIS. Classification of Evidence: This study provides Class IV evidence showing that adding maraviroc to the management of iatrogenic iPML/PML-IRIS does not improve the outcome.